Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1111/joa.12906
|View full text |Cite
|
Sign up to set email alerts
|

Associated tympanic bullar and cochlear hypertrophy define adaptations to true deserts in African gerbils and laminate‐toothed rats (Muridae: Gerbillinae and Murinae)

Abstract: Hearing capabilities in desert rodents such as gerbils and heteromyids have been inferred from both anatomical and ecological aspects and tested with experiments and theoretical models. However, very few studies have focused on other desert‐adapted species. In this study, a refined three‐dimensional morphometric approach was used on three African rodent tribes (Otomyini, Taterillini and Gerbillini) to describe the cochlear and tympanic bullar morphology, and to explore the role of phylogeny, allometry and ecol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(29 citation statements)
references
References 71 publications
3
26
0
Order By: Relevance
“…It was found that those otomyine species inhabiting regions with lower annual rainfall exhibited auditory bullae with larger volumes. This matched what was found by Nengovhela et al (2019) and we build on that study with the additional finding that this trend of inflated bullae in more arid regions is also found within a single, widely‐distributed species.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…It was found that those otomyine species inhabiting regions with lower annual rainfall exhibited auditory bullae with larger volumes. This matched what was found by Nengovhela et al (2019) and we build on that study with the additional finding that this trend of inflated bullae in more arid regions is also found within a single, widely‐distributed species.…”
Section: Discussionsupporting
confidence: 92%
“…These small mammals cannot hide amongst dense grass in these dry, vegetation‐sparse regions, and thus communicating to their burrow‐mates of potential dangers is crucial in this environment (Walsberg, 2000). Specific tests for auditory ability in detecting particular frequencies have not been done for the otomyine rodents; however, studies of other rodents have indicated that bullar hypertrophy is linked with the detection of low frequency sounds (Manoussaki et al, 2008; Nengovhela et al, 2019; Vater & Kössl, 2011; West, 1985).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study compiled data from various analyses of 3D composite images of 174 crania of 16 rodent species from two muroid families (Muridae, Cricetidae) assem-bled from two published studies (cochlea: Nengovhela et al 2019;endocranial volume: Nengovhela et al 2023) and hitherto unpublished data from our research group (brain structure and turbinate bones). A deeper insight into the role of ecological adaptations requires a narrow phylogenetic context and correction for the effects of body size.…”
Section: Discussionmentioning
confidence: 99%
“…2015; Nengovhela et al. 2019). This trend of increasing bulla size in desert rodents is usually explained by a perceived greater auditory sensitivity to low‐frequency (LF) sounds in open environments generated either by prey or by conspecifics (Lay 1972, Alhajeri et al.…”
Section: Introductionmentioning
confidence: 99%